357 Bridging the gap between reality and genetic potential in pig performance by nutritional strategies. (5th December 2019) - Chen, Daiwen; Zheng, Ping; che, lianqiang; Yu, Bing
Abstract: The global pork output in 2018 reached over 100 million tons and will continue to grow. However, great gap still exists between current productivity and the full genetic potential of pigs. Our hypothesis was that current nutritional profile could not meet the pig biological requirement, and that modifying nutritional strategies can maximize their genetic potential. To test this hypothesis, three experiments were conducted using fluid feed, fermented feed, and modified nutrient profile, respectively. Experiment 1 utilized 360 DLY weaning piglets with 6 replicate pens per treatment and 30 pigs per pen. Piglets were fed either a solid feed or a fluid feed with the exact same formulation. Results showed that fluid feed significantly increased ADFI by 53% from 245 to 375 g/d and increased ADG by 54% from 183 to 281 g/d from d 23 to 30 (P < 0.001). Experiment 2 utilized DLY weaning piglets fed 3 dietary treatments: Corn-SBM control, control + 75 mg/kg chlorotetracycline, and 12h-fermented control diet with 6 replicate pens per treatment and 3 pigs per pen. Results showed that 12h fermentation significantly increased ADG from 374 to 474 g/d from 35–56 d, reduced FCR from 1.74 to 1.52, and reduced diarrhea occurrence from 24.4% to 6.6% compared to control (P < 0.015). Performance from the fermentation group was also significantly better than the chlorotetracycline group. Experiment 3 utilized 8 individually-housed PIC pigs fed modified nutrient profile to determine performance from 7 to 147 days of age. Results showed that BW reached 26.5, 33, 100, 112.6 kg on d 60, 70, 134, 147, respectively, and overall FCR was 1.93. Results from these experiments demonstrated that the genetic potential of pig can be realized in greater extend by nutritional strategies.